GIS based evaluation of the production system of a sugar factory - Nagy, Ildikó; Takács, Péter (Acta Agraria Kaposváriensis, 2006)
Technological development enables for more and more middle and large sized agricultural firms to store their data about their production on computers. Most database are stored in GIS-based systems, which have several advantages: handling and visualizing data with geographic coordinates; capability to use various data formats (digital soil and cadastre maps, remotely sensed images, field measurements, etc.); geostatistical analyses can be performed. In our article we intrude the first steps of building the Eastern Sugar Ltd.’ complex GIS database in the area of the sugar factory at Kaba.
Keywords: sugar factory crop production system; GIS data base; data integration